(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
Coastal areas of Bangladesh are more susceptible to the adverse effects of climate change due to their geographic location and geological condition. The coastal zones and offshore islands of the country have indisputably experienced the combined consequences of global temperature and sea level rise. Aiming to study and understand shoreline dynamics and shoreline change, medium resolution (30m) satellite imagery over 30 (1990-2020) years was being executed. The Digital Shoreline Analysis System (DSAS) in the GIS platform was used in conjunction with other geospatial techniques to ascertain shoreline dynamics in multiple satellite images taken over this period, and afterward, the spatial outcomes were validated through a detailed field investigation. The study demarcated that the shoreline of Moheshkhali is subjected to severe erosion and accretion and has undergone significant morphological changes. On the basis of average shoreline change rates, the island’s shoreline is divided into 6 accretion zones and 4 erosion zones, with accretion being the dominant process. Accretion occurs in the south and south-western parts of the island, particularly those near the sea heads, which have experienced significant accretion at a rate of more than 86 m/yr and the consequent westward and south-east migration of the shore due to the active deposition along the coast. Besides, minor alterations were observed in the north and north-eastern part of the island. The study also evident that climate change, windy storms, variability in coast material, intermittent wave and air action, longshore transport, and anthropogenic activities are prime factors that contribute to the highly dynamic nature of the shorelines of Moheshkhali island. Therefore, this study demonstrates the benefit of using an integrated GIS-DSAS tool to investigate spatiotemporal shoreline change, and it might be valuable in land-use planning and coastal erosion mitigation on Moheskhali Island. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022, P 1-13